2005
DOI: 10.1002/crat.200410484
|View full text |Cite
|
Sign up to set email alerts
|

Why CuInGaSe2 and CdTe polycrystalline thin film solar cells are more efficient than the corresponding single crystal?

Abstract: Recently, very high conversion efficiencies in thin film polycrystalline solar cells have been reported. In particular it was reached an efficiency record both for CuInGaSe 2 (CIGS) and CdTe that are 19.2% and 16.5% respectively. We will briefly describe the technological methods used to fabricate these thin film solar cells. Besides, we will try to explain the reason why thin film polycrystalline devices can achieve conversion efficiency comparable with those shown by single crystal solar cells (mono-Si or po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 15 publications
(14 reference statements)
0
18
0
Order By: Relevance
“…CdTe/CdS solar cells with the highest conversion efficiency of 16.5% have been prepared using the CSS method [8]. It is reported that polycrystalline CdTe/ CdS solar cells perform better than single-crystal CdTe/ CdS cells [9]. Solar cells have been widely used in satellites, space stations and space vehicles as power sources, which operate in radiation environments.…”
Section: Introductionmentioning
confidence: 99%
“…CdTe/CdS solar cells with the highest conversion efficiency of 16.5% have been prepared using the CSS method [8]. It is reported that polycrystalline CdTe/ CdS solar cells perform better than single-crystal CdTe/ CdS cells [9]. Solar cells have been widely used in satellites, space stations and space vehicles as power sources, which operate in radiation environments.…”
Section: Introductionmentioning
confidence: 99%
“…DSSCs are photovoltaic devices that present the advantage of being fabricated through low-cost processes and do not require photoactive materials with a high degree of purity [1]. However, their efficiency is generally lower than the best-performing thin film solar cells based on IV-VI semiconductors (CdTe~16 %, CIGS~19 % lab efficiency) [3] and crystalline silicon (~23 % lab efficiency) [4]. In the case of conventional DSSCs, dye sensitization involves solely the semiconductor anode made of ntype TiO 2 nanoparticles [1,5].…”
Section: Introductionmentioning
confidence: 99%
“…Where is the photon flux to the Air Mass Coefficient (AM) of spectrum in standard PV modules test conditions referenced AM 1.5 [9][10][11][12][13].…”
Section: Theorymentioning
confidence: 99%